Targeting the integrated stress response in ophthalmology. (3rd August 2021) - Chu, Hsiao-Sang; Peterson, Cornelia; Jun, Albert; Foster, James
ABSTRACT: Purpose: To summarize the Integrated Stress Response (ISR) in the context of ophthalmology, with special interest on the cornea and anterior segment. Results: The ISR is a powerful and conserved signaling pathway that allows for cells to respond to a diverse array of both intracellular and extracellular stressors. The pathway is classically responsible for coordination of the cellular response to amino acid starvation, ultraviolet light, heme dysregulation, viral infection, and unfolded protein. Under normal circumstances, it is considered pro-survival and a necessary mechanism through which protein translation is controlled. However, in cases of severe or prolonged stress the pathway can promote apoptosis, and loss of normal cellular phenotype. The activation of this pathway culminates in the global inhibition of cap-dependent protein translation and the canonical expression of the activating transcription factor 4 (ATF4). Conclusion: The eye is uniquely exposed to ISR responsive stressors due to its environmental exposure and relative isolation from the circulatory system which are necessary for its function. We will discuss how this pathway is critical for the proper function of the tissue, its role in development, as well as how targeting of the pathway could alleviate key aspects of diverse ophthalmic diseases.